(untitled) (Canadian Medical Education Journal, 2025)
Background: Feedback remains essential to a learner’s professional development. Most feedback literature focuses on provision of feedback, and there is a lack of evidence-based data to support learners in developing skills to receive, evaluate and use feedback, independently of context. This scoping review mapped the literature regarding strategies and skills that optimize medical learners’ reception to feedback. Methods: Investigators conducted searches in MEDLINE, Embase, ERIC, APA PsycINFO and Web of Science Core collection from inception to May 2023. Study inclusion criteria were primary evidence sources, and strategies or skills for improved feedback reception for medical learners. Data were screened and extracted by pairs of independent reviewers. Investigators summarized study characteristics, outcomes, educational methods, and interventions. Results: Of 6915 total studies, six provided strategies and skills to improve feedback reception. Delivery of education was via workshops (n = 5 studies) that proposed cognitive, reflective and experiential learning activities, all reporting learners’ self-perceived improvement of feedback behaviour. Nine strategies and seven tools were identified, focusing on general approach, soliciting or evaluating feedback. Conclusion: The six included studies outline nine strategies and seven skills for improved learner feedback reception, focusing on overall approach and agentic behaviours without evaluation of the strategies or skills in practice. Key concepts and gaps in the literature were identified and may guide further investigation to optimize learner reception to feedback.